2015
DOI: 10.1186/s12889-015-2174-7
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on peripheral arterial disease in a district of Sri Lanka: prevalence and associated factors

Abstract: BackgroundPeripheral arterial disease (PAD), a slowly progressive atherosclerotic disease affecting vital organs of the body, is increasingly recognized as a health burden worldwide. Epidemiological information on peripheral arterial disease is scarce in Sri Lanka. The present study intended to estimate the prevalence and associated factors of PAD among adults aged 40–74 years in Gampaha district, Sri Lanka.MethodsA cross-sectional study was carried out to estimate the prevalence of PAD among adults aged 40–74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…The cutoff levels of ABPI for selection of cases and controls were based on the finding of a validation study of ABPI [12]. All the cases of our study were incident cases detected during the community based prevalence survey [11]. As latent period of PAD is long, modification of risk factors following diagnosis becomes a major drawback if prevalent cases were selected for a case control study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cutoff levels of ABPI for selection of cases and controls were based on the finding of a validation study of ABPI [12]. All the cases of our study were incident cases detected during the community based prevalence survey [11]. As latent period of PAD is long, modification of risk factors following diagnosis becomes a major drawback if prevalent cases were selected for a case control study.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster size was 28 with equal number of males and females. Detailed methodology of this cross sectional survey has been described in previously published paper [11]. Identification of cases and controls was based on ankle brachial pressure index (ABPI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] According to a recent study based on outpatient data, the prevalence of PAD in the US population more than 65 years of age is 11.8% and the incidence 22.4 per 1000 person-years. 4 A recent epidemiological study from Sri Lanka reported the incidence of PAD among general population aged between 40-74 years at 3.6% with no significant gender difference [5]. Worldwide, the disease affects nearly 2% of general population over the age of 40 years.…”
Section: Background and Epidemiologymentioning
confidence: 99%
“…Peripheral arterial disease (PAD) is one of the most common cardiovascular diseases in developed countries [ 1 ] and is an emerging problem in developing countries [ 2 , 3 ]. The Trans-Atlantic Inter-Society Consensus reported the prevalence of PAD in European population studies ranged from 3.6 to 9.2 %, and was 10–20 % in those aged over 70 years [ 4 ].…”
Section: Introductionmentioning
confidence: 99%